Banana Plantation, Trinidad - (:unkn) unknown (My University, 2009)
A lone labourer stands among the banana "trees" on a plantation.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bananas--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Plantations--Trinidad and Tobago